Potential interactions between cannabinoids and estrogens in common diseases - Hojnik, Marko; Dobovišek, Luka; Ferk, Polonca (Acta Medico-Biotechnica, 2021)
Molecular associations between the cannabinoid system and estrogens have recently been discovered. This research field is particularly interesting because it could lead to new pharmacotherapeutic approaches, especially in diseases where both molecular systems contribute to the pathophysiology. This paper presents an overview of the role of the cannabinoid system and estrogens in osteoporosis, atherosclerosis and cancer, and discusses the potential benefits of the modulating both systems in the pharmacotherapy of these diseases. Although an extensive literature review points to likely interactions between the cannabinoid system and estrogens, appropriate molecular studies have not yet been carried out. Our recent results in primary human osteoblasts are the first to demonstrate a possible interaction between the two systems at a molecular level. Further studies are needed to carefully examine molecular interactions as well as the efficacy and safety of various combinations of estrogens and cannabinoids in the pathogenesis and pharmacotherapy of osteoporosis, atherosclerosis, cancer and other common diseases.